The effect of management commitment to service quality on job embeddedness and performance outcomes - M. Karatepe, Osman; Karadas, Georgiana (Journal of Business Economics and Management, 2012)
The purpose of this study is to develop and test a conceptual model that examines job embeddedness as a partial mediator of the impact of management commitment to service quality on service recovery performance and extra-role customer service. Training, empowerment, and rewards are regarded as the three important indicators of management commitment to service quality. Data were obtained from a sample of fulltime frontline hotel employees with a time lag of one week in Romania. The results reveal that training, empowerment, and rewards are positively related to job embeddedness. As hypothesized, empowerment, rewards, and job embeddedness enhance service recovery performance, while training and empowerment increase extra-role customer service. The results further demonstrate that job embeddedness acts as a partial mediator of the effects of empowerment and rewards on service recovery performance. Implications of the results are discussed and future research directions are offered.